2015
DOI: 10.18632/oncotarget.5773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of normobaric oxygen and melatonin on reperfusion injury: role of cerebral microcirculation

Abstract: In order to protect the brain before an irreversible injury occurs, penumbral oxygenation is the primary goal of current acute ischemic stroke treatment. However, hyperoxia treatment remains controversial due to the risk of free radical generation and vasoconstriction. Melatonin is a highly potent free radical scavenger that protects against ischemic stroke. Considering its anti-oxidant activity, we hypothesized that melatonin may augment the survival-promoting action of normobaric oxygen (NBO) and prevent bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 31 publications
5
41
0
1
Order By: Relevance
“…In a previous study, we demonstrated for the first time that melatonin activated Akt phosphorylation following FCI in mice [14], which was later shown in various tissues, including brain [4], [5], [15], seminiferous tubules [31] as well as in cancer cells [32]. Melatonin-induced apoptosis of cancer cells is intervened by Pi3K/Akt pathway [32].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a previous study, we demonstrated for the first time that melatonin activated Akt phosphorylation following FCI in mice [14], which was later shown in various tissues, including brain [4], [5], [15], seminiferous tubules [31] as well as in cancer cells [32]. Melatonin-induced apoptosis of cancer cells is intervened by Pi3K/Akt pathway [32].…”
Section: Discussionmentioning
confidence: 87%
“…It detoxifies oxygen-and nitrogen-based free radicals and oxidizing agents, including the highly toxic hydroxyl-and peroxynitrite radicals, initiating lipid peroxidation and neuronal injury [1], [2], [3]. It was previously revealed that melatonin reduced brain injury and DNA damage after ischemic stroke in rodents [4], [5]. So far, the neuroprotective effect of melatonin has been linked mainly to its direct free radical scavenging and indirect antioxidant activities [3].…”
Section: Introductionmentioning
confidence: 99%
“…The growing fetal brain requires an adequate supply of oxygen and nutrients, delivered throughout the brain via the concurrent development of the vast neurovascular network structure. Microvascular damage is reportedly reduced by MLT in response to brain hypoperfusion and reperfusion injury [32] , suggesting that MLT might exert a neuroprotective effect by protecting the microvessels themselves. Indeed there is evidence that MLT acts directly on vasculature to mediate blood flow to various vascular beds including the brain, to stabilize blood brain barrier integrity [33] , prevent endothelial cell dysfunction [34] , decrease nitric oxide and VEGF production, and suppress ischemia-induced cerebral edema [35] .…”
Section: Discussionmentioning
confidence: 99%
“…They reported that combined NBO and melatonin synergistically reduces neuronal injury after mild focal cerebral ischemia induced by 30-minute MCAO. Combination therapy of NBO and melatonin regulated levels of phosphorylated Akt, antiapoptotic Bcl-xL, pro-apoptotic Bax and endothelial NO synthase, as well as reduced neuronal injury, neurological deficits, infarct volume and BBB permeability which has been found by NBO and particularly melatonin treatment alone (Beker et al, 2015).…”
Section: Nbo Plus Melatoninmentioning
confidence: 78%